Effects of Conservation Tillage on Crop Yield： a Case Study in the Part of Typical Ecological Zones in China - TANG, Qiu-xiang; LI, Shao-kun; XIE, Rui-zhi; ZHANG, Jian-xin; REN, Tian-zhi; LIN, Tao; GAO, Shi-ju (Agricultural sciences in China, 2011)
To evaluate the effects of different conservation tillage modes on crop yield in various ecological regions, we interviewed peasant households in the Northeast China Plain, North China Plain, Chengdu Plain, and Northwest China Oasis, China, to analyze the influencing factors of the tillage methods on crop yield. An index set was determined from seven yield parameters based on expert consultation and relevant literature. A comprehensive evaluation of conservation tillage methods in the various ecological regions was carried out using fuzzy theory. The approaches with the highest scores were identified for each region: wide and narrow rotation planting with high stubble standing retention in the Northeast China Plain; seeding after rotary tilled of wheat under corn straw mulching and no-tillage seeding of corn and other crops under wheat straw mulching in the North China Plain; no tillage with high stubble retention in the Northwest China Oasis; and no-tillage seeding of wheat and other crops under rice straw mulching in Chengdu Plain. These research data provide a useful guide for the selection of conservation tillage methods for optimum yields in different regions of China.